Pengendalian Mutu Tahu dengan Checksheet, Diagram Pareto, dan Diagram Fishbone pada Usaha Tahu Tansa - Muhammad Arsil Adhim; Faryal Virgiana Cikal Rukmana; Aulia Nursyifa Setiawan; Alyana Mevia Zahra; Lasma Rintan Antonia Pasaribu; ⁠Fany Apriliani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the product quality of tofu at Tahu Tansa, a tofu business located in Bogor City, by utilizing quality control tools such as check sheets, Pareto diagrams, and fishbone diagrams. Tofu is a nutritious food product with high consumer demand, but its production process often encounters defects that affect product quality. This research uses primary data obtained through direct observation and interviews and is analyzed using descriptive quantitative methods. The results show that the most dominant defect is non-standard tofu cutting size (50%), followed by overly soft texture (37.87%), and residual cloth stuck on the product (12.13%). Based on fishbone analysis, these defects are caused by suboptimal factors including manpower, machines, methods, raw materials, and measurement. The findings imply that improvements in operational standards, workforce training, and strict monitoring of raw materials and equipment are necessary to maintain quality and improve production efficiency at Tahu Tansa.